(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The DELHI MILK SCHEME has five different sections, which has a variety of electrical machines and instruments installed according to the plant need. The purpose of this paper is to providing a brief idea about presently installed machines, instruments with their working methodology and capacity along with a comparison of their ideal working states. The Electrical Department controls the power supply of heavy machines and other aid regarding machines. Despite of other instruments the Electrical Department of DMS has using most of the step down transformers to providing the appropriate power supply to the plant systems and 3-phase induction motor to run them with auto transformer and star delta starter, to protect these machines from any fault the circuit breakers and relays of distinct rating are used. The Instruments Section provides the essential sensors and other measuring devices. The Refrigeration Section handles the refrigeration process of cold storage and provides cooling water as an agent to maintain the temperature of the posturizing and other machines. The Boiler department provides the steam for the pasteurization process of milk. Poly pack Sect ion handles the packing of milk